Impact of a DSS-supported medication review on the safety of drug therapy and quality of life in patients with antithrombotic therapy - Hassanzadeh, Tanja Elnaz; Hohmann, Carina; Culmsee, Carsten (Frontiers in Pharmacology, 2024)
Polypharmacy is common among patients with antithrombotic medication, giving rise to concerns about Drug-Related Problems (DRPs). Therefore, these patients would benefit from a Medication Review (MR) along with pharmacist counselling to reduce the risks accompanying polymedication. This prospective study presents a concept for MRs that are applicable in German community pharmacies and can efficiently support pharmacist counselling and improve the safety of drug therapy.As this is a major challenge in everyday pharmacy practice, we used a Decision Support System (DSS) to evaluate its ability to support the process of pharmacist-led MRs. The primary endpoint was the impact of a community pharmacist on the reduction of DRPs. We investigated the impact of the interventions resulting from MRs on patients taking at least one antithrombotic drug as part of their polymedication regimen. Secondary endpoints were the reduction in the number of patients with bleeding risks and the improvement of patients' Quality of Life (QoL) and therapy adherence.Furthermore, the DSS used in the study was controlled for correct data assessment and plausibility of data. We selected adult patients who were taking no less than three different medications for long-term treatment, at least one of which had to be an antithrombotic drug, and who were customers in one of eight selected pharmacies over a period of six months. Data from 87 patients were analyzed with DSS-support. A total of 234 DRPs were identified by the pharmacist (2.7 DRPs per patient). MR reduced DRPs by 43.2% which, resulting to a reduction of 1.2 DRPs per patient. The intervention also led to a significant improvement in the patients' QoL (assessed via EQ-5D-5L questionnaire; p < 0.001) and enhanced therapy adherence (assessed via A14 questionnaire; p < 0.001). The control of correct data assessment (with 93.8% concordance) and plausibility of data (with 91.7% concordance) of the DSS software were conducted by an external auditor. No significant effect was found for overall bleeding risk. The results of this study indicate that DSS-supported and structured MR conducted by pharmacists can contribute to a reduction in DRPs and significantly improve patient's QoL and adherence to treatment.